Process analytical technology based monitoring and control of crystal properties in pharmaceutical crystallisation processes. - Abu Bakar, Mohd Rushdi; Nagy, Zoltan K. (IIUM Press, 2011)
Crystallization is an important unit operation used in a variety of industries. Its importance in the pharmaceutical industries is due to a large number of active pharmaceutical ingredients that are utilised in solid form. It is estimated that more than 80% ofpharmaceutical products involve at least one crystallization step in their manufacturing process (Reutzel-Edens, 2006). The pharmaceutical crystallisation operation is often critical because it determines the product properties, such as the crystal size distribution, morphology and polymorphic form. These properties in tum influence the efficiency of the subsequent downstream operations, particularly filtration and drying. The properties also affect the therapeutic performance ofthe product, such as dissolution rate and bioavailability. A proper control of crystallization processes offers possibilities for improved process efficiency and better product quality